PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Survei pada Karyawan PT. Asia Recycle Mandiri) - Rejeki, Sari Tri; Suprayitno, Suprayitno; Sutarno, Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
The purpose of this study was to analyze the significance of the influence of leadership style, work motivation, work discipline on the performance of employees of PT. Asia Recycle Mandiri. This study uses survey methods, the type of data used are qualitative and quantitative data, the source of the data used are primary data and secondary data. The population of this research is the employees of PT. Asia Recycle Mandiri with 115 employees. A sample of 50 employees using cluster random sampling proportional technique. Methods of data collection using questionnaires and documentation. The data analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The results of the study concluded that there was a significant influence of leadership style on the performance of employees of PT. Asia Recycle Mandiri. There is a significant influence of work motivation on the performance of employees of PT. Asia Recycle Mandiri. There is a significant influence of work discipline on the performance of the employees of PT. Asia Recycle Mandiri.